In Vitro antiproliferative potential of essential oil extract from Carica papaya L. seeds against cervical cancer - Sayed Nady, Doaa; Abdel-Halim, Sally A.; Hegazy, Mohamed-Elamir F.; Aljohani, Salwa; AlRashidi, Aljazi Abdullah; El-Desouky, Mohamed A.; Ahmed, Hoda A.; Jaremko, Mariusz; Emwas, Abdul-Hamid; Hanna, Demiana H. (Frontiers in Pharmacology, 2025)
IntroductionCervical cancer, the third most common cancer worldwide, is primarily caused by human papillomavirus (HPV) infection. This study aimed to develop natural extracts from the seeds of Carica papaya L. using the hydrodistillation method to evaluate their anticancer effects against HeLa cells.MethodsThe phytochemical composition of Carica papaya seeds’ essential oil was identified using gas chromatography mass spectrometry, and their cytotoxicity on proliferation, apoptosis, cell cycle phases, migration, and colony formation of HeLa cancer cell lines was examined. Moreover, the effects of essential oil on the protein expression levels related to apoptosis, cell cycle regulation, and migration in the treated HeLa cells were examined.Result and discussionThe essential oil’s phytochemical composition was analyzed using gas chromatography-mass spectrometry (GC-MS), revealing benzyl isothiocyanate as the dominant compound (99.49%). Results demonstrated that the essential oil had a high cytotoxic effect, with an IC50 value of 16.78 µg/mL in the MTT assay. Apoptosis analysis indicated a significant increase in early and late apoptotic HeLa cells (23.45%). Flow cytometry revealed a G2/M phase arrest, which impeded cell division. The oil also exhibited a stronger inhibition of cancer cell migration (38.7%) than methotrexate (45.9%). Additionally, the clonogenic assay revealed a drastic reduction in colony formation (0.004% surviving fraction, 0.25% plating efficiency). ELISA results showed a profound effect on apoptosis-related proteins, reducing BCL-2, MMP-2, and CDK1/cyclin B1 expression, supported by molecular docking studies comparing its efficacy to methotrexate (−5.52, −6.29, and −5.75 vs −5.49, −5.44, and 5.18 kcal mol−, respectively). The findings suggest that Carica papaya seed essential oil may serve as a potential anticancer treatment for cervical cancer; however, further in vivo studies are required for validation in animal models.